IMPROVING STUDENT PARTICIPATION AT SDN22/X KUALA SIMBUR BY USING PROJECT BASED LEARNING IN ENGLISH SUBJECT - KARISMA, SARIFA; Sari, Junita; Warni, Warni; Arliana, Arliana (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2024)
This research investigates the application of the Project Based Learning (PjBL) model to enhance active participation among elementary school students in English learning. Using a Classroom Action Research design with McTaggart’s model, the study was conducted in one cycle consisting of six meetings. Data collection was performed through teacher observations and field notes to capture student engagement and participation throughout the learning process. The research aimed to address the low level of student activity and interest in traditional English learning methods. The findings reveal that the implementation of PjBL significantly improved student participation. Of the 21 students observed, 19 actively engaged in group discussions, project activities, and presentations. The remaining two students showed progress, though their involvement was less consistent. The PjBL model encouraged students to explore, collaborate, and produce creative outputs, such as a mini dictionary, which allowed them to apply English vocabulary in a meaningful context. The structured PjBL syntax fostered critical thinking, teamwork, and confidence among the students. This study concludes that PjBL is an effective approach for creating an engaging and inclusive learning environment. It provides educators with a practical framework for increasing student motivation and participation, offering a meaningful and interactive alternative to conventional teaching methods.